Sociophonetic analysis of phonemic trill variation in two sub-varieties of Peninsular Spanish. Issue 1 (March 2014) - Henriksen, Nicholas
Abstract : In this paper we provide a preliminary characterization of the phonemic trill (i.e., /r/) as produced by twenty-four speakers of northern and central Peninsular Spanish. The acoustic analysis revealed a considerable number of non-canonical variants containing one or zero apical occlusions. The quantitative results showed robust effects of the following three factors on trill articulation: Speaker dialect, gender, and preceding vowel. Regarding social factors, central Peninsular speakers and male speakers showed the greatest propensity to produce fewer occlusions per phonemic trill. Regarding linguistic factors, non-canonical variants were especially common in contexts of preceding /u/; we interpret this result on articulatory grounds given the antagonistic gestures required for the trill and the high back vowel. All in all, these findings offer empirical support that geographically-oriented studies within a sociophonetic framework offer critical information on the diachrony of trill consonants.